2020
DOI: 10.1590/fst.08919
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of the physicochemical characteristics from Melipona subnitida D. honey in adequation to Brazilian law

Abstract: The honey samples were obtained by direct and indirect contact with producers from different localities in the cities of Ceará State

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…The acidity which is a remarkable characteristic of the flavor, associated with the maturation state of honey (Braga et al, 2020) did not change in our study over the course of 4 years. The variation of acidity among different samples which was reported in the literature may be due to the variations in floral type of plants (Küçük et al, 2007) and harvest season (Singh & Bath, 1997).…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…The acidity which is a remarkable characteristic of the flavor, associated with the maturation state of honey (Braga et al, 2020) did not change in our study over the course of 4 years. The variation of acidity among different samples which was reported in the literature may be due to the variations in floral type of plants (Küçük et al, 2007) and harvest season (Singh & Bath, 1997).…”
Section: Resultscontrasting
confidence: 43%
“…In our study, no variation was observed in the HMF content with passage of time. Braga et al (2020) found higher divergence of some patterns such as HMF, moisture, and acidity as compared to the the legislation standards.…”
Section: Resultsmentioning
confidence: 74%
“…Even during the rainy season, high temperatures and a decrease in air relative humidity may eventually occur [23]. SBH produced in different regions of the semi-arid northeastern region of Brazil (Caatinga zone) displayed moisture content values ranging from 23.17% to 28.9% (w/w) [24][25][26]. Biluca et al, (2016), reported that SBH from the Atlantic Forest zone showed high moisture content (23.1% to 43.5%, w/w) [27].…”
Section: Physicochemical Characterization Of Sbhmentioning
confidence: 99%
“…Brazilian honey has been recognized for its quality that also depends on the aforementioned factors and the region where it is produced (Braga et al, 2019). This quality presents variations in quantity and type of phenolic compounds, as well as in flavor and aroma.…”
Section: Introductionmentioning
confidence: 99%